Faktor-Faktor yang Berhubungan dengan Pencegahan Covid-19 pada Ibu Hamil di Wilayah Kerja Puskesmas Rumbia - Achmad Hilal (Journal of Health Quality Development, 2021)
COVID-19 is a newly discovered disease, therefore knowledge related to its prevention is being explored by world scientists. The purpose of the study was to determine the factors related to the prevention of COVID-19 in pregnant women in the working area of ??the Rumbia Health Center. The type of research used is a cross sectional study. The sampling technique was purposive sampling. The results of the research that have been conducted found that there is a relationship between knowledge and prevention of COVID-19 in pregnant women in the working area of ??the Rumbia Health Center, there is a relationship between attitude and prevention of COVID-19 in pregnant women in the working area of ??the Rumbia Health Center, there is a relationship between education and prevention of COVID-19 in mothers. pregnant in the working area of ??the Health Center. In conclusion, there is a relationship between knowledge, knowledge and education with the prevention of COVID-19 in pregnant women in the working area of ??the Rumbia Health Center.